Seed biometric parameters in oil palm accessions from a Brazilian germplasm bank - Camillo, Julcéia; Braga, Valentine Carpes; Mattos, Jean Kleber de Abreu; Lopes, Ricardo; Cunha, Raimundo Nonato Vieira da; Padilha, Joseane; Scherwinski‑Pereira, Jonny Everson (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the morphological diversity of oil palm seeds and to cluster the accessions according to their morphological characteristics. Forty‑one accessions from the oil palm germplasm bank of Embrapa Amazônia Ocidental were evaluated – 18 of Elaeis oleifera and 23 of E. guineensis. The groups were formed based on morphological characteristics, by principal component analysis. In E. oleifera, four groups were formed, tied to their region of origin, but with significant morphological differences between accessions from the same population. For tenera‑type E. guineensis seeds, three widely divergent groups were formed, especially as to external parameters, which differentiated them from the other ones. The parameter endocarp thickness stood out in intra‑ and inter‑population differentiation. For dura‑type E. guineensis, three groups were formed, with larger seeds and thicker endocarps, which differed from all the other ones. The variability observed for seed characteristics in the analyzed accessions allows the establishment of different groups, to define strategies for genetic improvement.